Comparing the Effectiveness of Cognitive Behavioral Therapy and Schema Therapy on Self-Coherence in Adolescents with High-Risk Behaviors - Ghafari Moghadam, Fahimeh; Dehghani-Arani, Fateme; Zarghami, Elham (Mental Health and Lifestyle Journal, 2026)
The present study aimed to compare the effectiveness of cognitive behavioral therapy and schema therapy on self-coherence in adolescents with high-risk behaviors. This applied study employed a quasi-experimental design with a pretest–posttest format, including a control group and a follow-up phase. The statistical population consisted of adolescents with high-risk behaviors referred to counseling centers of the Department of Education in Karaj in 2025. A total of 45 participants were selected through purposive sampling based on inclusion criteria and were randomly assigned, after matching demographic characteristics, into two experimental groups and one control group (15 participants in each group). One experimental group received cognitive behavioral therapy and the other received schema therapy across eight structured sessions, while the control group remained on a waiting list. Data were collected using the Integrative Self-Knowledge Questionnaire at three time points: pretest, posttest, and two-month follow-up. Data analysis was conducted using SPSS-27 through descriptive statistics, multivariate analysis of variance, repeated measures analysis of variance, and Bonferroni post hoc tests after verifying statistical assumptions. The results indicated that the main effect of group on self-coherence was not statistically significant (p = 0.440), whereas the main effect of time (p < 0.001) and the interaction effect of time and group (p < 0.001) were statistically significant. Bonferroni post hoc comparisons revealed that both cognitive behavioral therapy and schema therapy groups showed significantly higher self-coherence scores compared to the control group at posttest (p < 0.05), while no significant difference was found between the two experimental groups (p > 0.05). Pairwise comparisons across time demonstrated significant improvements from pretest to posttest and from pretest to follow-up in both intervention groups (p < 0.05), with no significant differences between posttest and follow-up, indicating stability of treatment effects. Both cognitive behavioral therapy and schema therapy were effective in enhancing self-coherence among adolescents with high-risk behaviors, and their effects were maintained over time, although no significant superiority of one approach over the other was observed.